Persepsi Masyarakat Tanjung Rejo Kecamatan Medan Sunggal Terhadap Pemberitaan Media Massa Tentang Virus Corona - Jaka Syahputra; Dedi Sahputra; Ilma Saakinah Tamsil (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2022)
At the beginning of 2020 the world was shocked by the Corona virus, information circulating about the Corona virus came from Wuhan, China. The Corona virus has caught the public's attention and caught the attention of the mass media. Many people do not know Covid-19, therefore they seek information on Covid-19 through the media.The purpose of this study was to determine the Tanjung Rejo community’s perception of the mass media coverage of the Corona virus. The theory used in this research is theory of perception and theory of uses and effect. The method used is a qualitative approach and face-to-face interviews with the people of Tanjung Rejo to collect the data. The data analysis technique used in this research is a qualitative approach. This research is descriptive, and describes the object of research as it is based on facts. This research is an attempt to reveal news issues related to the Corona virus or the circumstances of events that actually occurred. The results of this study indicate that the Tanjung Rejo community's perception of mass media reporting about the Corona virus is that some people are very afraid of excessive reporting that is informed by the mass media because media is reporting too much about the Corona virus